(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2021)
The preliminary measurements using a Triple to Double Coincidence Ratio (TDCR) Liquid Scintillator Counter System developed by the Nuclear Metrology Laboratory (LMN) at IPEN, is presented. The TDCR system makes use of three photomultipliers positioned at 120° relative angle, operating in coincidence. For this preliminarymeasurement, 14C was selected to be standardized; 14C was chosen due to be a pure beta emitter with low end-point energy of 156 keV, which is suitable to be measured by the TDCR system. This solution was previously calibrated by the efficiency tracing technique using a 4p(PC)b-g coincidence system, employing 60Co as a tracer. The activity of the 14C solution by efficiency tracing technique was determined by using the extrapolation technique, changing the beta efficiency by pulse height discrimination. In order to determine the final activity, a Monte Carlo simulation was used to generate the extrapolation curve. The Software Coincidence System (SCS) developed by the LMN was used for both systems to register the events. MICELLE 2 code was used to calculate the theoretical TDCR efficiency. Measurements using HIDEX, a commercial liquid scintillator system, were also carried out and the results from the three methods were compared, showing a good agreement.